D‐dimer use for deep venous thrombosis exclusion in elderly patients: a comparative analysis of three different approaches to establish cut‐off values for an assay with results expressed in D‐dimer units. (16th January 2014) - Cini, M.; Legnani, C.; Frascaro, M.; Sartori, M.; Cosmi, B.; Palareti, G.
Summary Introduction The use of adapted cut‐off values in the elderly, combined with clinical probability (PTP), increases the proportion of patients in whom venous thromboembolism (VTE) can be safely excluded, compared with the conventional cut‐off value of 500 μg/L fibrinogen equivalent units (FEU). We evaluated the clinical performance of three different approaches to establish cut‐off values for a D‐dimer assay whose results are expressed in D‐dimer units (D‐DU). Methods HemosIL D‐dimer HS assay (Instrumentation Laboratory) was performed in 279 consecutive outpatients with suspected deep venous thrombosis (DVT) and nonhigh PTP. Results Considering patients >60 years, the number of negative D‐dimer results increased using the modified (376 ng/mL if ≥60 years) and the age‐adjusted cut‐off (age years × 5 ng/mL if >50 years) compared to the conventional one (230 ng/mL for all patients; 54.6%, 58.2%, and 25.0%, respectively), with no false‐negative results. The higher increase was observed in patients >80 years (43.9%, 56.1%, and 8.8%, respectively). Conclusion For the HemosIL D‐dimer HS, the use of specific cut‐off values in older subjects with suspected DVT and nonhigh PTP increases the number of patients in whom DVT can be safely excluded.